Effect Of Ethanol, Hexane And Water Extracts Of Clinacanthus Nutans Leaves On Hone-1 Proliferation - Moehamad Orliando Roeslan; Siti Ladia Fatima (Jurnal Kedokteran Gigi Terpadu, 2020)
Background: Mortality from cancer has increased especially in the developing country. Global pattern shows the half of mortality occurred in Asia. One type of cancer occurring in Indonesia is nasopharyngeal cancer. Clinacanthus nutans is a species of herbal plants in the Acanthaceae family that grows in tropical Asia, especially Indonesia. This plant is considered as one of traditional medicinal plants, which is effective in treating several diseases, including cancer. Different polarity of solvent that used to extract this plant will have different dissolved compounds. Objective: To determine the effect of ethanol, hexane, and water extract of C. nutans leaves on HONE-1 cell proliferation.Method: This study conducted using experimental research in vitro laboratory. Three different extract, ethanol, hexane, and water extract of C. nutans leaves treated to HONE-1 cell. Cell proliferation was measured using MTT assay.Result: The results showed significant differences (p <0.05) of treatments group compared to negative control. Ethanol extract showed the highest inhibition of HONE-1 cell proliferation.Conclusion: Ethanol, hexane, and water extract of C. nutans leaves could inhibit the HONE-1 cell proliferation